2021
DOI: 10.1017/s0030605321000818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the first 10 years of the Cambridge Masters in Conservation Leadership

Abstract: Conservation lacks sufficient well-trained leaders who are empowered to catalyse positive change for the natural world. Addressing this need, the University of Cambridge launched a Masters in Conservation Leadership in 2010. The degree includes several features designed to enhance its impact. Firstly, it recruits international, gender-balanced cohorts of mid-career professionals, building leadership capacity in the Global South and providing a rich environment for peer learning. Secondly, teaching includes app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The mismatch between the skills that are taught to students and the skills required in biodiversity conservation and management positions (Blickley et al, 2013; Bonine et al, 2003; Lucas et al, 2017; Muir & Schwartz, 2009) has led to the development of a handful of conservation leadership courses that aim to cover both technical and soft skills (e.g. Sandbrook et al, 2021). While these courses have a very positive impact, their overall effect is confined due to their operational scale or attendance costs (in addition to their location in only a few countries).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mismatch between the skills that are taught to students and the skills required in biodiversity conservation and management positions (Blickley et al, 2013; Bonine et al, 2003; Lucas et al, 2017; Muir & Schwartz, 2009) has led to the development of a handful of conservation leadership courses that aim to cover both technical and soft skills (e.g. Sandbrook et al, 2021). While these courses have a very positive impact, their overall effect is confined due to their operational scale or attendance costs (in addition to their location in only a few countries).…”
Section: Discussionmentioning
confidence: 99%
“…Training on the design of monitoring programmes and how they can be linked to and inform management objectives and actions should be a standard module of conservation courses and yet monitoring design is conspicuous by its absence from these (e.g. Gardner, 2021; Sandbrook et al, 2021; Van Heezik & Seddon, 2005). Such courses, which are mostly designed by academics, could benefit from codevelopment with practitioners or draw from research such as ours to ensure that they more closely align with on the ground capacity needs outside the academic setting.…”
Section: Discussionmentioning
confidence: 99%
“…The Capacity Building for Conservation Conference series (in 2013, 2015, 2017 and 2019) has been an important first step in this process. This conference series has resulted in numerous outcomes, such as new collaborations, new funding relationships, improved communication, as well as the articles comprising this special theme in Oryx focused on conservation capacity development (Appleton et al, 2021; Sandbrook et al, 2021; Sterling et al, 2021; Abu-Bakarr et al, 2022; Bruyere et al, 2022; Campagnaro et al, 2022; Chao et al, 2022; Gerrie et al, 2022; Loffeld et al, 2022a,b; O'Connell et al, 2022; Porzecanski et al, 2022).…”
Section: Key Theme 4: Building Strong Relationships Between Donors An...mentioning
confidence: 99%
“…This will be critical for developing capacity in areas where local communities are affected severely by the loss of biodiversity but where conservation approaches also need to be decolonized (Domínguez & Luoma, 2020). This will also require diverse, effective and resilient leaders (Sandbrook et al, 2021; Webb et al ., 2021). These individuals and their institutions need both technical and functional capacities, but these leaders will also require less tangible skills such as being relational and reflective, trust-building, visioning and problem-solving (Black, 2021; Abu-Bakarr et al, 2022; Campagnaro et al, 2022; Loffeld et al, 2022b).…”
mentioning
confidence: 99%
“…These have been shown to promote supportive practice that can encourage application of skills and knowledge within learning communities (Bruyere et al, 2022) and enable innovation and upscaling. A number of established conservation leadership development programmes have found that experiential learning opportunities combined with peer network development are effective (Sandbrook et al, 2021; Abu-Bakarr et al, 2022). Additionally, creating safe spaces for peer-supported learning and development helps practitioners build resilience, experiment with a wider range of approaches, accept and learn from failure, and enhance creativity and innovation (Dickson et al, 2022; Loffeld et al, 2022a).…”
mentioning
confidence: 99%